Kompetensi dan kinerja karyawan: Peran moderasi iklim organisasional - Wahyudi, Wahyudi; Rozi, Achmad; Putry, Miranti (Jurnal Manajemen Maranatha, 2022)
The achievement of the company's vision and mission has been previously determined from the company's resources, especially human resources. Employees are the activator of every company activity, therefore the company's success depends on its employees. Collaboration between employees and company management become important for the achievement of organizational goals. The purpose of this study was to investigate the relationship between competence, organizational climate, and employee performance, where the moderating variable of organizational climate is used in this study.  Data were collected from questionnaires that had been filled out by respondents with a total 110 employees of PT. Selaras Donlim Indonesia, and then processed using SmartPLS 3 software with the Partial Least Squares Structural Equation Modeling (PLS-SEM) procedure. The results of this study support the three hypotheses proposed, where competence and organizational climate directly affect on employee performance significantly. Beside that, the moderating effect of organizational climate could strength competence in influencing employee performance significantly, the strength of the moderating effect is discussed.